2022
DOI: 10.3390/jcm11020421
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide COVID-19-EII Study: Incidence, Environmental Risk Factors and Long-Term Follow-Up of Patients with Inflammatory Bowel Disease and COVID-19 of the ENEIDA Registry

Abstract: We aim to describe the incidence and source of contagion of COVID-19 in patients with IBD, as well as the risk factors for a severe course and long-term sequelae. This is a prospective observational study of IBD and COVID-19 included in the ENEIDA registry (53,682 from 73 centres) between March–July 2020 followed-up for 12 months. Results were compared with data of the general population (National Centre of Epidemiology and Catalonia). A total of 482 patients with COVID-19 were identified. Twenty-eight percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Our results are broadly similar with data published in the literature. European data from the first wave of the pandemic were also in favor of a low incidence of SARS-CoV-2 infection in patients with IBD, with slightly more hospitalizations but no severe infection ( 17 , 18 ). In a study led in 24 Italian IBD centers in a region particularly affected during the first wave of the pandemic in Europe with more than 140,000 cases in March 2020 and more than 18,000 deaths, only 79 positive patients were reported, with 6 deaths (7%), in which anti-TNF was not a risk factor (odds ratio [OR] 0.4; 95% CI 0.04-3.78; p=0.42) ( 40 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results are broadly similar with data published in the literature. European data from the first wave of the pandemic were also in favor of a low incidence of SARS-CoV-2 infection in patients with IBD, with slightly more hospitalizations but no severe infection ( 17 , 18 ). In a study led in 24 Italian IBD centers in a region particularly affected during the first wave of the pandemic in Europe with more than 140,000 cases in March 2020 and more than 18,000 deaths, only 79 positive patients were reported, with 6 deaths (7%), in which anti-TNF was not a risk factor (odds ratio [OR] 0.4; 95% CI 0.04-3.78; p=0.42) ( 40 ).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported a lower prevalence of SARS-CoV-2 infection in the IBD population, with a trend towards more frequent hospitalizations without increasing the risk of severe COVID-19 infection and admission in intensive care unit ( 17 21 ). Data in patients with IBD also tend to show a protective effect of anti-TNF agents ( 22 24 ), but there is still some uncertainty on the subject ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Subsequent studies have largely shown that IBD does not increase the risk of SARS-CoV-2 infection or worse COVID-19 outcomes. [3][4][5][6][7][8] Data have also confirmed that biologic and novel small molecule therapies are not associated with worse COVID-19 outcomes. 9,10 Furthermore, vaccines against SARS-CoV-2 are effective in reducing symptomatic or severe COVID-19, and early data have shown that in patients with IBD, vaccine efficacy is comparable with that in the general population.…”
Section: Introductionmentioning
confidence: 87%
“…They found that age >60 years (OR 7.1) and >2 comorbidities (OR 3.9) were associated with mortality which, was 3.7% in the cohort. Interestingly, the use of steroids in the previous 3 months before COVID-19 diagnosis was the only predictor of physical sequelae such as myalgia, arthralgia, and asthenia at 3 months [ 5 ]. To evaluate the impact of COVID-19 on the psychiatric health of IBD patients, Ryu et al performed an electronic survey in South Korea and found significant anxiety and depression related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%